The value of new drugs for advanced prostate cancer. Issue 18 (1st June 2021) - Howard, David H.; Quek, Ruben G. W.; Fox, Kathleen M.; Arondekar, Bhakti; Filson, Christopher P.
Abstract : Background: The US Food and Drug Administration has recently approved a number of new cancer drugs. The clinical trials that serve as the basis for new cancer drug approvals may not reflect how the drugs will perform in routine practice and do not measure the impact of the drugs on spending. The authors sought to evaluate the real‐world effectiveness and value of drugs recently approved for advanced prostate cancer. Methods: Using Surveillance, Epidemiology, and End Results–Medicare data, the authors identified fee‐for‐service Medicare beneficiaries aged 65 years or older who began treatment with a drug approved for metastatic castration‐resistant prostate cancer in 2007‐2009, when only 1 drug was approved for metastatic castration‐resistant prostate cancer, and in 2014‐2016, when 5 additional drugs were approved. They calculated life expectancy and lifetime medical costs (ie, Medicare reimbursements) for each group. Results: Between 2007‐2009 and 2014‐2016, life expectancy increased by 12.6 months. Lifetime medical costs increased by 87, 000. The incremental cost per life‐year gained was 83, 000. Conclusion: The release of 5 new drugs coincided with increases in survival rates and spending. This study's estimates indicate that the new drugs collectively were cost‐effective. Abstract : Surveillance, Epidemiology, and End Results–Medicare data have been used to calculate changes in survival and spending between 2007‐2009 and 2014‐2016 among Medicare beneficiaries aged 65 years or older with metastatic castration‐resistant prostate cancer. It is estimated that life expectancy has increased by 12.6 months and that lifetime medical costs have increased by 87, 000.